Полифонијата во творештвото на Димче Николески создадено во периодот 1960-1980 година - Јовиќ, Тихомир (Интернационален унивезитет ЕУРОПА ПРИМА, 2021)
Dimche Nikoleski (village of Kosel, Ohrid region, January 13, 1943 - April 2, 1998, Skopje) is one of the generations of Macedonian composers whose division mainly takes place in the seventies and eighties of the twentieth century. Although he lived relatively short (55 years), Dimche Nikoleski’s creative path is very intense and creative, which is reflected not only in the sphere of his musical creation, but also in the spheres of music journalism and social action in general. Dimche Nikoleski’s musical work is primarily focused on chamber music. In the period 1960-1980, his work included 36 genre-diverse works. The aim of this paper is to explain the approach of the author to the polyphonic syllable as a principle of organization of musical material. In particular, the research will be aimed at determining the type, manner and scope of use of polyphony in the work of Dimche Nikoleski created in the above twenty-year period. For this purpose a corpus was formed from the available works (scores and recordings) by the author.
Keywords: Dimche, Nikoleski, polyphony, polyphoniforms